Characterization of seafloor marine litter distribution in a shipping route of Ancon bay - Rázuri Esteves, Víctor Fernando (2022)
Marine litter on the seafloor has been increasing for several decades. Moreover, shipping routes and fishing ports are considered as affected areas with benthic macro-litter distribution. In Peru, the available information about benthic litter is limited and only originates from cleaning campaigns. Therefore, this study aimed to conduct the first scientific report about benthic macro-litter occurrence and composition distributed in a shipping route of Ancon Bay. For this purpose, a remotely operated vehicle (ROV) was used to evaluate the marine litter composition and distribution at depths between 1 and 25 m. A total of 8.8 h of video transects were recorded, and 46 litter items were identified, where plastic represented 80.4%; and industry food and single-use bags were the most frequent items. Plastic fragments and food industry bags dominated areas closer to San Francisco Grande mud sandy beach and the anchorage zone, respectively, while non-plastic items were more common in front of rocky shores. The present work emphasizes the importance of the studies about benthic marine debris for better decision-making regarding litter management. It also highlighted the usefulness of low-cost ROVs in identifying different litter items in shallow areas.